THE IMPLEMENTATION OF KNOW-WANT-LEARN (K-W-L) STRATEGY IN TEACHING READING AT ELEVENTH GRADE OF SMA NEGERI 3 SINGARAJA - Putra, I. P. K. A. P. (Language and Education Journal Undiksha, 2019)
This study aimed at describing the implementation of K-W-L (Know-Want-Learn) strategy used by one of the English teachers in SMA Negeri 3, Singaraja. In this study, the subjects of the study were the students of SMA Negeri 3 Singaraja especially the eleventh grade and an English teacher. The present study employed qualitative design. The methods of data collection were classroom observation and questionnaire. The findings showed that there were 3 stages of the implementation of K-W-L (Know-Want-Learn) strategy namely pre-teaching, whilst-teaching and post-teaching. The result of the questionnaire, it means about the brilliant alternative strategy used by teacher, because KWL (Know-Want-Learn) developed some ideas about the text before reading the whole text and focus to find the important points of the text. Before the student starts to read the text, they need to use their prior knowledge and continue to set their want or interest of the text.